Heterogeneity, leveling the playing field, and affirmative action in contests - Chowdhury, S; Esteve-González, P; Mukherjee, A (University of Oxford, 2020)
The heterogeneous abilities of the players in various competitive contexts often lead to undesirable outcomes such as low effort provision, lack of diversity, and inequality. A range of policies are implemented to mitigate such issues by enforcing competitive balance, i.e., leveling the playing field. While a number of such policies are aimed at increasing competition, affirmative action (AA) policies are historically practiced in an ethical response to historical discrimination against particular social groups among winners. This survey summarizes the rapidly growing literature of contest theory on AA and other policies that level the playing field. Using a general theoretical structure, we outline research on player and contest designer behavior under a multitude of policy mechanisms; and discuss the theoretical, experimental, and empirical results in relation to some of the common debates surrounding AA.